IMPLEMENTASI PERATURAN KOMISI PEMILIHAN UMUM NOMOR 4 TAHUN 2015 PADA PENETAPAN DAFTAR PEMILIH TETAP PEMILIHAN WALIKOTA DAN WAKIL WALIKOTA SAMARINDA TAHUN 2015 DI KOMISI PEMILIHAN UMUM KOTA SAMARINDA - Sapinah Sapinah (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACT In the system of Election in Indonesia, one could choose if already registered in the voters list (DPT), because it concerns the right to choose a person to make choices and express their aspirations in general elections. The purpose of the study is to examine the implementation of the legislation, especially the General Elections Commission Regulation No. 4 of 2015 on voter data collection process and any obstacles encountered in the field to ensure the eligibility of voters. The method used normative juridical-empirical collection of primary data obtained directly from field research and interviews with sources in related institutions, namely the Commission of Samarinda, while secondary data from the library research.PKPU No. 4 of 2015 on implementation as guidelines for updating the voters have been effective for the accuracy of data being generated, the problems that arise in the process Determination of the voters list have also been followed up by the Commission Samarinda, and during the administration of elections and local elections since 2004 have never been there the voting public who take legal actions related concerned are not enrolled in DPT. KPU Kota Samarinda and its staff should improve further the performance and coordination so that the results of updating voters' data in the future to be better and the accuracy of the resulting data becomes more valid, the community must participate oversee and supervise the process of updating the voter data to produce accurate data and valid. Keywords        :   Implementation, Regulation Election Commission, voters list, the General Election Commission